Progress and Development of Capture for CO2 by Ionic Liquids - A Review - Zhang, L.; Chen, J.; Lv, J.X.; Wang, S.F.; Cui, Y. (Asian Journal of Chemistry, 2012)
Ionic liquids have attracted considerable attention used as green solvents because they have excellent properties, such as no volatility, stability, good solubility and adjustable structures. This review describes the recent development of ionic liquids for CO2 capture and separation, including room-temperature ionic liquids, task-specific ionic liquids, supported ionic-liquids membranes and polymerized ionic liquids and discusses the mechanism of the absorption and introduced combined technologies of room temperature ionic liquid and other solvents for CO2 capture. Finally, the application outlook of ionic liquids is prospected.